How to win friends and influence people - Carnegie, Dale 1888-1955 (Pocket Books, 1981)
A revised edition of the best-selling guide to interpersonal relationships provides suggestions for successfully dealing with people both in social and business situations. You can go after the job you want and get it! You can take the job you have and improve it! You can take any situation you're in and make it work for you! For over 50 years the rock-solid, time-tested advice in this book has carried thousands of now famous people up the ladder of success in their business and personal lives. Now this phenomenal book has been revised and updated to help readers achieve their maximum potential in the complex and competitive 90s! Learn: The six ways to make people like you. The twelve ways to win people to your way of thinking. The nine ways to change people without arousing resentment and much, much more! You can go after the job you want ... and get it! You can take the job you have and improve it! You can take any situation you're in and make it work for "you!" For over 50 years the rock-solid, time-tested advice in this book has carried thousands of now famous people up the ladder of success in their business and personal lives. Now this phenomenal book has been revised and updated to help readers achieve their maximum potential in the complex and competitive 90s! Learn: The six ways to make people like you. The twelve ways to win people to your way of thinking. The nine ways to change people without arousing resentment and much, much more!